The Impact of Health Programs on Lifestyle Changes in Diabetic Patients - Arfah, Arfah; Susianti, Susianti; Mansur, Narti (Journal of Asian-african Focus in Health, 2024)
This study explores the impact of health programs on lifestyle changes in diabetic patients, focusing on the role of education, behavioral counseling, and continuous support in improving health outcomes. Diabetes mellitus, a chronic condition affecting millions worldwide, requires effective management strategies to prevent complications such as cardiovascular diseases and kidney failure. A quantitative approach was employed, surveying 300 diabetic patients enrolled in health programs that included nutritional education, physical activity guidelines, and medication adherence support. The study utilized multiple regression and ANOVA to analyze the data. Results revealed significant improvements in dietary compliance, physical activity, medication adherence, and clinical markers such as HbA1c levels, weight, and blood pressure. Behavioral counseling, particularly motivational interviewing and cognitive-behavioral therapy, was found to significantly enhance lifestyle adherence. Additionally, continuous monitoring via telemedicine platforms improved patient engagement and long-term lifestyle changes. These findings highlight the importance of multifaceted interventions in diabetes management and address existing gaps in the literature by identifying the key components of successful health programs. The study also emphasizes the sustainability of lifestyle changes and the growing potential of digital health tools in chronic disease management. However, the research acknowledges limitations such as reliance on self-reported data and the homogeneity of the sample. Future research should explore diverse populations and utilize objective measures of health outcomes to further validate these findings